Transcriptomic and proteomic analyses of core metabolism in Clostridium termitidis CT1112 during growth on α-cellulose, xylan, cellobiose and xylose. Issue 1 (December 2016) - Munir, Riffat; Spicer, Victor; Krokhin, Oleg; Shamshurin, Dmitry; Zhang, XiangLi; Taillefer, Marcel; Blunt, Warren; Cicek, Nazim; Sparling, Richard; Levin, David
Abstract Background Clostridium termitidis CT1112 is an anaerobic, Gram-positive, mesophilic, spore-forming, cellulolytic bacterium, originally isolated from the gut of a wood feeding termiteNasusitermes lujae . It has the ability to hydrolyze both cellulose and hemicellulose, and ferment the degradation products to acetate, formate, ethanol, lactate, H2, and CO2 . It is therefore ges in gene and gene product expression during growth ofC. termitidis on cellobiose, xylose, xylan, and α–cellulose. Results Correlation of transcriptome and proteome data with growth and fermentation profiles identified putative carbon-catabolism pathways inC. termitidis . The majority of the proteins associated with central metabolism were detected in high abundance. While major differences were not observed in gene and gene-product expression for enzymes associated with metabolic pathways under the different substrate conditions, xylulokinase and xylose isomerase of the pentose phosphate pathway were found to be highly up-regulated on five carbon sugars compared to hexoses. In addition, genes and gene-products associated with a variety of cellulosome and non-cellulosome associated CAZymes were found to be differentially expressed. Specifically, genes for cellulosomal enzymes and components were highly expressed on α–cellulose, while xylanases and glucosidases were up-regulated on 5 carbon sugars with respect to cellobiose. Chitinase and cellobiophosphorylases were the predominant CAZymes expressed on cellobiose. In addition to growth on xylan, the simultaneous consumption of two important lignocellulose constituents, cellobiose and xylose was also demonstrated. Conclusion There are little changes in core-metabolic pathways under the different carbon sources compared. The most significant differences were found to be associated with the CAZymes, as well as specific up regulation of some key components of the pentose phosphate pathway in the presence of xylose and xylan. This study has enhanced our understanding of the physiology and metabolism ofC. termitidis, and provides a foundation for future studies on metabolic engineering to optimize biofuel production from natural biomass.